2018
DOI: 10.1002/dneu.22633
|View full text |Cite
|
Sign up to set email alerts
|

Glial Cell Expansion Coincides with Neural Circuit Formation in the Developing Auditory Brainstem

Abstract: Neural circuit formation involves maturation of neuronal, glial and vascular cells, as well as cell proliferation and cell death. A fundamental understanding of cellular mechanisms is enhanced by quantification of cell types during key events in synapse formation and pruning and possessing qualified genetic tools for cell type-specific manipulation. Acquiring this information in turn requires validated cell markers and genetic tools. We quantified changing proportions of neurons, astrocytes, oligodendrocytes, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
38
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 12 publications
(39 citation statements)
references
References 79 publications
1
38
0
Order By: Relevance
“…In our previous work, we found evidence that proliferation of MNTB astrocytes occurred during the perinatal period that precedes hearing onset [11]. Other groups have reported proliferation of oligodendrocytes in the mouse MNTB [14]. Future studies could evaluate the localization of proliferating astrocytes and oligodendrocytes with respect to the vasculature.…”
Section: Discussionmentioning
confidence: 71%
See 1 more Smart Citation
“…In our previous work, we found evidence that proliferation of MNTB astrocytes occurred during the perinatal period that precedes hearing onset [11]. Other groups have reported proliferation of oligodendrocytes in the mouse MNTB [14]. Future studies could evaluate the localization of proliferating astrocytes and oligodendrocytes with respect to the vasculature.…”
Section: Discussionmentioning
confidence: 71%
“…The MNTB consists of a population of principal neurons that are innervated by the calyces of Held, specialized glutamatergic synaptic terminals that originate from cochlear nucleus globular bushy neurons (Figure 1A) [8]. Recent studies showed significant changes in the development of MNTB astrocytes, oligodendrocytes and microglia during the postnatal period that precedes hearing onset, which in rats occurs around postnatal day 12 (P12) [10][11][12][13][14][15]. However, to the best of our knowledge, the development of the MNTB vasculature has not been characterized in any species.…”
Section: Introductionmentioning
confidence: 99%
“…Studies indicate that the intermediate filament GFAP is a marker for mature astrocytes (Eng et al, 1971; Pixley and de Vellis, 1984; Wofchuk and Rodnight, 1995) as well as for reactive astrocytes, as GFAP immunostaining peaks 1 week after bilateral cochlear ablation in the CN of rats (Fuentes-Santamaria et al, 2013, 2017). In the auditory brainstem, glial cell expansion coincides with neural circuit development (Brandebura et al, 2018) and astrocytic markers appear at distinct times during postnatal development. In the MNTB, ALDH1L1-positive cells are present at P0, while S100β expression is sparse and GFAP expression is completely absent.…”
Section: Discussionmentioning
confidence: 99%
“…Type 2 spines, in contrast to type 1 spines, contain organelle structures and can be tortuous and very thin at many locations along their length, so the substrates may exist for multiple modes of communication from electrically and chemically isolated compartments. These signaling modes may mediate synaptic plasticity and local processing within the spine mat that communicates among the intertwined neuronal and glial processes as glial and neuronal elements transform structurally into a mature circuit (Brandebura et al, 2018;Dinh et al, 2014;Holcomb et al, 2013;Rodríguez-Contreras et al, 2008;Saliu et al, 2014).…”
Section: Intercellular Communicationmentioning
confidence: 99%